Physical and Chemical Quality of Corn Husks with Ammoniation, Biofermentation and Ammonia Fermentation Processing - Farda, Fitria Tsani; Liman, Liman; Erwanto, Erwanto; Muhtarudin, Muhtarudin; Sirat, Muhammad Mirandy Pratama; Fathul, Farida; Ramadhan, Doni (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
This study aimed to evaluate the processing of ammoniated, biofermented and amorphous corn husks on physical quality, dry matter, ash content, crude protein (CP), ether extract (EE), crude fiber (CF), and nitrogen free extract (NFE). This study used a completely randomized design (CRD) which consisted of 4 treatments and 4 replications. The treatments given were P1: untreated corn husks (control), P2: ammoniated corn husks (2% urea), P3: fermented corn husks (5% Aspergillus niger), and P4: amofered corn husks (2% urea + 5% Aspergillus niger). The variables observed included physical quality and nutrient content (dry matter, ash, crude protein, ether extract, crude fiber, and nitrogen free extract). The data obtained analyzed using Analysis of Variety and followed by Duncan's Multiple Range Test (DMRT). The results of the study had a significant effect on the physical quality, dry matter, ash, crude protein, ether extract, crude fiber and nitrogen free extract (P<0,05), but had no effect (P>0,05) on the ash content. Amopheric processing has the best effect on physical quality, crude protein and crude fiber content of corn husks. Fermentation processing gives the best effect on ether extract and nitrogen free extract.